Circular economy practices in the hotel sector: a change of paradigm (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
Traditionally the hotel industry has been developing a production and consumption model that responds to a linear system extracting more resources than the planet can generate, produces, uses and finally throws away, forming large amounts of waste, which implies the need to transform its current system of production and consumption,  through the implementation of circular economy practices aligned with the principles of sustainable tourism, aimed at reducing pollution, contributing to sustainable growth, preservation of natural resources and respect for the environment, improving the ecosystem, the balance between progress and sustainability, increasing the value and profitability of the company. From this perspective, this research focuses its interest in conducting a literature review in recent years on the application of circular economy practices in the hotel sector at national and international level, through a descriptive literature review methodology. The results identified theorists who have addressed this topic over time and the companies that have begun to apply the good practices of circular models that contribute to sustainability and profitability and the need for many companies belonging to the sector under study to change the paradigm by replacing linear models with circular ones, implementing environmentally friendly actions to achieve more sustainable and profitable companies. The background review demonstrated the need for regulators to create incentives for the promotion of cleaner production that bets on more sustainable hotels.
Keywords: Circular economy; linear economy; hotels; paradigm; profitability; sustainability